Investigation of different socioeconomic levels parental experience to improve creativity in preschool period - Polat, Aslı Yıldırım; ÖZER, MERVE (My University, 2019)
One of the skills that a child needs to develop in pre-school is creativity. Although it is known that creativity comes from birth, the fact that everyone is at different levels shows that there are factors affecting the development of this skill. One of these factors is the parent. In the literature, there are researches on how children's creativity changes according to variables such as age, gender and socioeconomic level. However, no research has been achieved on what parents do to improve their children's creativity. The aim of this study is to reveal the experiences of parents in developing pre-school children's creativity. In this research, phenomenology is used. Participants were determined by criterion sampling from purposeful sampling methods and interviewed with six parents at two sub, two middle and two upper socioeconomic levels. As a result of the content analysis, it was observed that parents did similar activities in developing creativity with their children regardless of their level of education, but they were more creative by using the opportunities of parents at low socioeconomic level, while parents with a high socioeconomic level were more prone to getting ready to produce with their children. Parents should therefore be encouraged to develop creativity.
Keywords: Pre School Period; Children; Parent; Creativity; Çocuklar; Ebeveyn; Yaratıcılık